Unraveling the mysteries of a costoclavicular block: A case report - Sonawane, Kartik; Dixit, Hrudini; Balavenkatasubramanian, Jagannathan (Indian Journal of Case Reports, 2020)
The outcome of regional anesthesia with respect to the sensory and motor effects of local anesthetics has been a mystery to anesthesiologists. However, testing these effects is subjective with the currently available scoring/grading systems. We report an unusual case where the author himself is a patient, a 37-year-old male with no comorbidities, who underwent plating of distal radius fracture under costoclavicular block (CCB). He took this opportunity to record changes in the sensory and motor functions that he experienced until he regained them completely. This case report is a narration of his own experiences related to CCB during the perioperative period.